Increased urinary interleukin 22 binding protein levels correlate with lupus nephritis activity - Yang, Xuyan; Gao, Yin; Wang, Huiying; Zhao, Xiaoying; Gong, Xubo; Wang, Qingqing; Zhang, Xiaofei (Journal of rheumatology, 2014)
Interleukin 22 (IL-22) plays an important role in the promotion of antimicrobial immunity. However, dysregulated IL-22 action leads to inflammation and is involved in autoimmune diseases, including systemic lupus erythematosus (SLE). IL-22 binding protein (IL-22BP) is a soluble inhibitory IL-22 receptor and may represent a crucial regulator of IL-22. We investigated the expression and potential significance of serum and urinary IL-22BP levels in patients with SLE. A total of 112 patients with SLE and healthy control subjects participated in our study. Patients were classified according to kidney involvement and disease activity based on clinical and laboratory measures such as urinary sediment, proteinuria, kidney function, complement factor 3 (C3), C4, anti-dsDNA, disease activity index, and renal SLE disease activity index. The concentrations of IL-22BP and IL-22 were measured by ELISA. The expression of IL-22BP in the renal tissue was detected by immunohistochemistry. Patients with active renal disease had urinary levels of IL-22BP higher than (1) patients with active SLE but no renal involvement, (2) patients with a history of lupus nephritis in remission with no systemic disease activity and no history of renal involvement, and (3) control subjects. There was no difference in serum levels of IL-22BP among the groups. Urinary levels of IL-22BP in patients with active renal disease were positively correlated with SLE Disease Activity Index, Systemic Lupus International Collaborating Clinics renal activity score, and histological activity index. IL-22BP was highly expressed in renal tissue of patients with active renal disease. After 6 months of treatment, urinary IL-22BP levels decreased significantly in patients with complete response, but remained unchanged in those with partial or no response. Urinary but not serum IL-22BP levels were associated with active renal disease. Urinary levels of IL-22BP might be a potential marker for the presence of renal involvement in patients with SLE.